3D CNTs-threaded N-doped hierarchical porous carbon hybrid with embedded Co/CoOx nanoparticles as efficient bifunctional catalysts for oxygen electrode reactions. (1st December 2018) - Liu, Sa; Chen, Xiaowen; Wang, Si; Yang, Zheng; Gao, Jingxia; Zhu, Ping; Zhao, Xinsheng; Wang, Guoxiang
Abstract: Developing an efficient non-precious metal catalyst for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in regenerative energy conversion and storage devices is very imperative but still challenging. Herein, a three-dimensional (3D) hierarchical porous Co/CoO x nanoparticles embedded N-doped carbon hybrid threaded with carbon nanotubes (Co/CoO x @NC-CNTs) was prepared via in situ threading CNTs through ZIF-67 polyhedron and a succedent carbonation process. Compared to those of commercial electrocatalysts (Pt/C and RuO2 ), the as-prepared hybrid showed comparable electrocatalytic activity with positive ORR half-wave potential ( E 1/2 ) of 0.836 V, low OER potential ( E j=10  = 1.62 V), good methanol tolerance and excellent electrocatalytic stability. Moreover, the small overpotential difference value (Δ E  =  E j=10 - E 1/2 ) of 0.784 V is competitive to those of recent reported outstanding bifunctional oxygen electrocatalysts. The high electrocatalytic properties of the Co/CoO x @NC-CNTs hybrid are attributed to the synergistic effect of high surface area, desirable pore structure and reasonable chemical composition. Graphical abstract: A 3D hierarchical porous Co/CoO x embedded N-doped carbon hybrid threaded with carbon nanotubes was prepared as high efficient bifunctional catalysts for oxygen electrode reactions.